Caracterização físico-química e microbiológica das águas do rio Pericumã em Pinheiro-MA utilizada na irrigação. - Barroso, Solange Leitão (2007)
The research was developed between september/2004 and august/2005 with the objective to diagnose and analyse the rio Pericumãn’s water at Pinheiro-MA, under the physicochemical and microbiological aspects, that have a major value on the agronomic characterization of the water destination. The collects were monthly made in seven different locations among the river. The analyzed parameters were: temperature, conductibility, pH, turbidity, clorides, iron, ammoniacal nitrogen, nitrate, nitrite, sulfate. The microbiological parameters were: coliforms totais and coliforms thermotolerantes from the results, et mas concluded that there is a seasonal variation on rio Pericumãn’s water on the physicochemical parameters and that the colimetria during all the period of evolution is hight, invisiabiliting the irrigation of ram consumed pothers and fruits that still have pellicle.